Employing tetraethyl orthosilicate additive to enhance trap passivation of planar perovskite solar cells. (10th January 2019) - Guan, Mingjing; Zhang, Qianlong; Wang, Fei; Liu, Hongyu; Zhao, Junyi; Jia, Chong; Chen, Yiqing
Abstract: In this work, trap passivation can be enhanced by introducing the controlled tetraethyl orthosilicate (TEOS) additive into the perovskite precursor. The effect of different concentrations of TEOS additive on interfacial modification and carrier recombination process has been investigated systematically. Silicon dioxide (SiO2 ), the product of TEOS additive, can precipitate at the grain boundary after the formation of perovskite film, resulting in trap passivation at perovskite interface. The recombination kinetics manifests that a small amount of TEOS additive can significantly prolong carrier lifetime, due to the reduction of trap-states in the perovskite interface, which are supposed to be the carrier recombination centers. Using a typical planar structure of the cells prepared under fully open air condition, the steady-state efficiency of our best-performing devices has improved from 15.96 to 18.38%.